Cholestatic Jaundice as a Paraneoplastic Manifestation of Prostate Cancer - Tomomi Kuramoto; Hiroya Senzaki; Hiroyuki Koike; Kenji Yamagiwa; Shinobu Tamura; Tokuzou Fujimoto; Takeshi Inagaki (Case Reports in Urology)
Paraneoplastic syndrome associated with prostate cancer is extremely rare. We report a patient who presented with cholestatic jaundice without biliary duct obstruction, hepatic involvement, or infection. After a few detailed examinations, prostate cancer was diagnosed. After treatment with bicalutamide and leuprolide, the patient’s symptoms and laboratory abnormalities were reversed. Cholestatic jaundice was regarded as a paraneoplastic manifestation in this patient. The patient remains symptom-free after 14-month followup. Paraneoplastic syndrome should be considered in case of cholestatic jaundice without biliary duct obstruction, hepatic involvement, or infection.